EMAS SEBAGAI INVESTASI RENDAH RESIKO - Dian Ayu Rahmadani; Ida Ayu Putu Utami Paramita (Nusantara Hasana Journal, 2024)
The importance of investing is still not widely recognized by the public, even though facilities and conveniences for investing are already available or widely offered. The Indonesia Millennial Report states that 51% of millennials' money is spent on consumptive needs, 10.7% of funds are saved and only 2% for investment. From these data, it can be said that the millennial generation does not yet have an interest in investing. In fact, gold has a very high value and gold is the right investment vehicle and its existence as an investment vehicle even if there is an unstable economic turmoil. Investing in gold has the greatest advantage because its price tends to increase from year to year. This is a clear advantage for the owner, especially if the difference between the buying and selling prices is quite large. The importance of information about investment, in order to increase public insight and awareness to invest in gold.